Species of xyleborus (coleoptera: curculionidae: scolytidae) recorded in avocado trees in Colima, Mexico - Castrejón-Antonio, Jesús Enrique; Montesinos-Matías, Roberto; Acevedo-Reyes, Nallely; Tamez-Guerra, Patricia; Ayala-Zermeño, Miguel Ángel; Berlanga-Padilla, Angélica María; Arredondo-Bernal, Hugo César (Instituto de Ecología, A.C., 2017)
The presence of three ambrosia beetle species of Xyleborus genus (Curculionidae: Scolytinae) were recorded in avocado trees (Persea americana) from Colima, México; they were Xyleborus affinis Eichhoff, X. volvulus Fabricius, and X. spinulosus Blandford.